2009
DOI: 10.1002/cmdc.200900067
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of New PPARγ Agonists: Benzimidazole Derivatives – the Importance of Position 2

Abstract: Probing SAR: The 1-(biphenyl-4-ylmethyl)-1H-benzo[d]imidazole moiety is known to be an essential structural component of telmisartan for PPARgamma activation. This study focused on the substituents at position 2 of the benzimidazole in an attempt to optimize PPARgamma activation. In particular, the elongation of the alkyl chain and the introduction of an aromatic ring system were studied (shown).The relevance of substituents at C-2 of the central benzimidazole of telmisartan for PPARgamma activation has recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 14 publications
(15 reference statements)
0
18
0
Order By: Relevance
“…The compounds from this cluster follow the same pattern as cluster 1, but without the presence of an indole group. The sar8 [25], sar9 [26] and sar10 [27] series form cluster 4. The compounds from this cluster are derivatives of telmisartan, a compound that, in addition to being a PPARc partial agonist, is also a selective angiotensin II AT1 receptor blocker.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The compounds from this cluster follow the same pattern as cluster 1, but without the presence of an indole group. The sar8 [25], sar9 [26] and sar10 [27] series form cluster 4. The compounds from this cluster are derivatives of telmisartan, a compound that, in addition to being a PPARc partial agonist, is also a selective angiotensin II AT1 receptor blocker.…”
Section: Resultsmentioning
confidence: 99%
“…Binding features of partial agonists A total of 205 structures of PPARc agonists were retrieved from 12 SAR studies (sar1-12) of synthetic PPARc agonists (Table 1) [18][19][20][21][22][23][24][25][26][27][28][29]. Based on their chemical similarities, these 205 compounds can be grouped into five clusters (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, valsartan has a biphenyl-tetrazole group, but no imidasole groups. Goebel et al (46,47) also demonstrated the structural characterization of a PPARγ-activating ARB, telmisartan, and they showed that valsartan has no structure that docks to PPARγ. In general, all ARBs have similar structures, but a small structural difference may be important with respect to the PPARγ-activating property.…”
Section: Discussionmentioning
confidence: 99%
“…12 Furthermore, the alkyl chain in position 2 of the benzimidazole core, especially the propyl group, was important for potency and activation. 13 In continuation of our studies we investigated the significance of the positions 5 and 6 of the benzimidazole for PPARc modulating activity.…”
Section: Introductionmentioning
confidence: 99%